The Sticky Side of Hypocrisy: Environmental Activism in an Oil-Drenched World - Chang, Dave (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
Environmental activists and critics are often accused of being hypocrites by the oil industry.  The accusation unfurls from the view that the activists’ protests and actions contradict their espoused beliefs.  By presenting a simple thought experiment involving two alleged hypocrites, I discuss ways in which critics of environmental activists misapply the charge of hypocrisy, having neglected the contexts that determine the degree to which one is able to align one’s lived actions with one’s professed values.